Chest wall mechanics before and after diaphragm plication. Issue 1 (December 2016) - Elshafie, Ghazi; Acosta, Johanna; Aliverti, Andrea; Bradley, Amy; Kumar, Prem; Rajesh, Pala; Naidu, Babu
Abstract Background Following diaphragmatic plication for unilateral paralysis, the effect on global chest wall function are unknown. Our hypothesis was that chest wall function would improve in both sides of the chest after plication of the paralysed side. Case Presentation Using Optoelectronic Plethysmography, total and regional chest wall volumes were measured in one patient before and after left diaphragmatic plication. Volumes were recorded at quiet breathing. Respiratory capacity improved during quiet breathing when measured before and 6 months after surgery. These improvements occur at the abdominal-rib cage level in both operated and contralateral. Prior to surgery the abdominal rib cage motion was out of phase to the upper rib cage and abdominal compartment in both sides of the chest. Synchrony of all three compartments was restored after plication. Conclusion This physiological study is the first published data in humans to show improvement in chest wall motion both in operated and contralateral side following diaphragmatic plication for unilateral paralysis.